Modelling of steady state recycle chromatographic process. - Poon, Kit Bun. (2009)
The aim of this work is to model steady state recycle chromatography. The areas of work in this project can be classified into two parts. In the first part, modelling of a chromatographic column using mass balance was carried out. Parametric studies of the chromatography process were conducted to gain in-depth understanding of the effect of the parameters on the performance of the chromatography process. Validation studies were also conducted on the basic model based on linear and Langmuir isotherms. The basic model was used to benchmark the enantioseparation of 1-phenyl-1-propanol before progression into the next phase of the project.